Правове значення бюджету об’єднаної територіальної громади в системі місцевих бюджетів - Ананьєва, Є. А.; Ananieva, Ye. A.; ORCID: https://orcid.org/0000-0003-1459-6629 (Юридичний науковий електронний журнал. - 2023. - № 2. - С. 292-295, 2023)
Розглянуто основні терміни та визначення які характеризують план формування та використання фінансових ресурсів для забезпечення завдань і функцій органів місцевого самоврядування. Визначено правове значення місцевого бюджету. Наголошено, що бюджети місцевого самоврядування затверджуються рішенням відповідної ради, які і визначають бюджетні повноваження органів місцевої влади. Досліджено принцип самостійності бюджетної системи України, крізь призму місцевих бюджетів. З’ясовано які обмеження мають місцеві бюджети, керуючись принципом самостійності, а саме визначення видів та обсягів доходів та видатків, які регламентуються законом. З'ясовано різні визначення місцевих бюджетів, які характеризують їх з різних боків та мають різні характеристики і можуть виступати, як правова, економічна або соціальна категорія.

The article discusses the main terms and definitions that characterize the plan for the formation and use of financial resources to ensure the tasks and functions of local self-government bodies. But he emphasizes that the legislator provides the specified types of budgets taking into account the administrative structure of the country. The economic essence of the «minimum budget of local self-government» is considered, and it is emphasized that the minimum budget is used conditionally in practice, as an additional means of calculating the necessary finances. The legal significance of the local budget is considered, namely, it is emphasized that local self-government budgets are approved by the decision of the relevant council, which determines the budgetary authority of local authorities. The principle of independence of the budgetary system of Ukraine was studied through the prism of local budgets. It has been clarified what limitations local budgets have, guided by the principle of independence, namely the definition of the types and volumes of income and expenses, which are regulated by law. Different definitions of local budgets were considered in the article, which characterize them from different sides and have different characteristics and can act as a legal, economic or social category. Considerable attention was paid to the issues of formation of local budgets, their distribution and use. It was emphasized that the process of decentralization of power, proposed by the government to meet the needs of the regions, relies on local budgets, among which budgets of OTG have a new purpose, both as a financial plan and as a legal mechanism for the formation, distribution and use of local finances. The article also discusses the reform of local self-government. It was emphasized that at the beginning of the reform, most of the settlements of Ukraine, with the exception of some regional ones, had such a weak material and financial base that they were unable to provide the necessary public services in the respective territories, as well as to fulfill the powers of local self-government bodies. A number of circumstances that have developed in the regions and the country as a whole and that require consideration and changes to improve budgetary relations in the future have been studied.

Рассмотрены основные термины и определения, характеризующие план формирования и использования финансовых ресурсов для обеспечения задач и функций органов местного самоуправления. Определено правовое значение местного бюджета. Отмечено, что бюджеты местного самоуправления утверждаются решением соответствующего совета, которые определяют бюджетные полномочия органов местной власти. Исследован принцип самостоятельности бюджетной системы Украины, через призму местных бюджетов. Выяснены какие ограничения имеют местные бюджеты, руководствуясь принципом самостоятельности, а именно определение видов и объемов доходов и расходов, регламентируемых законом. Выяснены разные определения местных бюджетов, которые характеризуют их с разных сторон и имеют разные характеристики и могут выступать как правовая, экономическая или социальная категория.
The legal significance of the budget of the united territorial community in the system of local budgets
Ананьєва, Є. А. Правове значення бюджету об’єднаної територіальної громади в системі місцевих бюджетів [Електронний ресурс] / Ананьєва Є. А. // Юридичний науковий електронний журнал. - 2023. - № 2. - С. 292-295. – Режим доступу:http://www.lsej.org.ua/2_2023/66.pdf.
Keywords: Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; місцеве самоврядування; local governments; местное самоуправление; місцевий бюджет; local budget; местный бюджет; бюджет об’єднаної територіяльної громади; budget of the united territorial community; бюджет объединенной территориальной общины